Is the Relationship between Financial Development and Economic Growth Monotonic? Evidence from a Sample of Middle Income Countries - Nahla Samargandi; Jan Fidrmuc; Sugata Ghosh (Center for Economic Studies and ifo Institute (CESifo), 2014)
We revisit the relationship between financial development and economic growth in a panel of 52 middle income countries over the 1980-2008 period, using pooled mean group estimator in a dynamic heterogeneous panel setting. We show that financial development does not have a linear positive long-run impact on economic growth in this sample. When we consider a non-linear relationship between financial development and growth, we find an inverted U-shaped relationship between finance and growth in the long run. In the short-run, the relationship is insignificant. This finding suggests that middle income countries face a threshold point after which financial development no longer contributes to economic growth.
Keywords: C23; O11; O16; O47; 330; financial development; economic growth; heterogeneous panels; pooled mean group estimation; non-monotonicity